Civic Organizations, Sports Civic Organizations and the Control - Szabados, György Norbert; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Helmeczi, András; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2020)
Control, az a managerial function cannot be considered as one of the most frequently preferred examinational topics, and it is also valid for the matter of civic organization. Nevertheless, we must not forget about the increasing number and intensive non-profit sphere after the change of the regime, where the civic sphere inside has become determinant. In 2017, 15,2% of the 61 151 nonprofit organizations had a sport profile, and this ratio is higher, 16,2% regarding the 53 613 classic civic organizations (including only associations and foundations).  The specialty of these organizations is the strong relationship with subsidies, and it seems that it has turned into subsidy dependence by now (2/3 of the incomes are subsidies), as a conclusion from the data of the Hungarian Statistical Office. This topic may also become sensible in a way, when an organization cannot account the received subsidies or cannot meet expectations of the judicial expectations, which all raises managerial control related concerns. It also highlights the relationship between civic organizations and control. In this study, we aim to cover some relevant specifications of the topic through the control, as a managerial function, and based on the results we may conclude that a higher ratio of organizations cannot really perform by the expectations.